2021
DOI: 10.3389/fphar.2021.593682
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Cholinergic Anti-inflammatory Pathway Attenuated Angiotension II-Dependent Hypertension and Renal Injury

Abstract: Background: Angiotensin II (AngII) induces renal fibrosis, characterized by fibroblast proliferation, inflammatory cell infiltration and excessive extracellular matrix deposition, all of which was relevant closely to hypertension. The vagus nerve-related cholinergic anti-inflammatory pathway (CAP) modulates local and systemic inflammatory responses. The aim of present study was to determine the effect of CAP on renal inflammation and fibrosis.Methods and Results: AngII-induced hypertension was induced in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 61 publications
0
6
0
3
Order By: Relevance
“…Via an inflammatory reflex of the CAP, the vagus nerve perceives the peripheral inflammatory signal and then releases the neurotransmitter acetylcholine (Ach), which stimulates alpha 7 nicotinic acetylcholine receptor (α7nAchR) in multiple immune cells such as macrophage, and eventually inhibits the production of pro-inflammatory cytokines and cytokine-related devastating effects [ 6 , 7 , 8 ]. It has been widely studied that the activation of CAP, through stimulating the vagus nerve or activating α7nAchR receptor by a specific cholinergic agonist can effectively attenuate the development of various inflammatory diseases, including endotoxemia, rheumatoid arthritis, ischemia/reperfusion injury, and hemorrhagic shock [ 9 , 10 , 11 , 12 , 13 , 14 ]. Recent studies indicate that CAP may also play a functional role in the regulation of cardiovascular diseases such as atherosclerosis (AS), a chronic inflammatory condition [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Via an inflammatory reflex of the CAP, the vagus nerve perceives the peripheral inflammatory signal and then releases the neurotransmitter acetylcholine (Ach), which stimulates alpha 7 nicotinic acetylcholine receptor (α7nAchR) in multiple immune cells such as macrophage, and eventually inhibits the production of pro-inflammatory cytokines and cytokine-related devastating effects [ 6 , 7 , 8 ]. It has been widely studied that the activation of CAP, through stimulating the vagus nerve or activating α7nAchR receptor by a specific cholinergic agonist can effectively attenuate the development of various inflammatory diseases, including endotoxemia, rheumatoid arthritis, ischemia/reperfusion injury, and hemorrhagic shock [ 9 , 10 , 11 , 12 , 13 , 14 ]. Recent studies indicate that CAP may also play a functional role in the regulation of cardiovascular diseases such as atherosclerosis (AS), a chronic inflammatory condition [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The skin was incised along the right cervical line before the blunt dissection of the subcutaneous muscle layer. The right cervical vagal nerve was located in the carotid sheath, meticulously isolated by a glass needle, and cut off with ceramic scissors [ 20 ]. After the vagotomy, the incised skin was closed with interrupted sutures, and the rats were individually housed.…”
Section: Methodsmentioning
confidence: 99%
“…Baroreflex sensitivity is another marker of autonomic function having an important role in long-term development of hypertension. 50,51 Administration of GTS-21 to rats with angiotensin IIinduced hypertension improved baroreflex sensitivity and attenuated BP. Moreover, excessive renal fibrosis and overexpression of inflammatory cytokines were reduced (Fig.…”
Section: Hypertensionmentioning
confidence: 99%
“…In vitro investigations revealed that GTS-21 repressed nuclear factor κB (NF-κB) activation, decreased angiotensin II-induced epithelial-–mesenchymal transition, and lowered inflammation and fibrosis in NRK-52E cells. 51 Similar to α7-nAChR agonists, the acetylcholinesterase inhibitor donepezil produced beneficial effects for hypertension. 52 While both donepezil and pyridostigmine were able to improve cardiac vagal tone and prevent cardiac remodeling, only donepezil could reduce high BP and plasma cytokine levels in spontaneously hypertensive rats.…”
Section: Hypertensionmentioning
confidence: 99%